Changes in National Google Trends and Local Healthcare Utilization After High-Impact Gastroenterology Publications. (16th December 2021) - Kamboj, Amrit K.; Agarwal, Siddharth; Chedid, Victor G.; Iyer, Prasad G.; Bailey, Kent R.; Harmsen, William S.; Katzka, David A.
Abstract : INTRODUCTION: We examined national Google Trends and local healthcare utilization after 3 high-impact gastroenterology publications. METHODS: Changes in US Google Trends and Olmsted County health utilization were studied. RESULTS: Publication views within 30 days were 51, 458 ( Imperiale ), 49, 759 ( Pimentel ), and 18, 750 ( Gomm ). Colonoscopy searches ( P = 0.04) and Cologuard tests performed ( P < 0.01) increased while colonoscopies decreased ( P < 0.01). Searches for rifaximin ( P = 0.05), irritable bowel syndrome ( P < 0.01), diarrhea ( P < 0.01), and rifaximin prescriptions ( P = 0.02) increased. Increase in hydrogen-2 blocker searches ( P = 0.02) and prescriptions ( P < 0.01) and gastroesophageal reflux disease ( P < 0.01) and dementia office visits ( P < 0.01) occurred. DISCUSSION: High-impact gastroenterology publications influence Google searches and local population-based healthcare utilization.